Gender Identity Formation of Single Parent Children in Pinang Sebatang Barat Village, Tualang District, Siak Regency (Study Case: Single Parent Families and Gender Identity Formation) - Mulia, Sari Permata; Risdayati, Risdayati (CV. Rayyan Dwi Bharata, 2024)
This study was conducted in Pinang Sebatang Barat Village, Tualang District, Siak Regency. This study aims to identify how single mothers and fathers shape the gender identity of children aged 3-7 years through their roles as caregivers, educators, and breadwinners. This study involved 6 subjects, consisting of 5 single mothers and 1 single father, selected using purposive sampling techniques. The theory used in this study is Albert Bandura's social learning theory, which looks at the process of forming children's gender identity through observation, imitation, and behavioral reinforcement. This study uses a qualitative method with a descriptive approach, as well as a case study research type. Data collection techniques are carried out through in-depth interviews, observation, and documentation. To ensure data validity, researchers also use triangulation methods to compare results from different methods and sources. The results of this study indicate that single mothers and fathers have challenges in shaping children's gender identity, especially in modeling masculine or feminine gender roles. Limited time and economic resources are often obstacles for single parents in carrying out parenting and education functions, so that some children are cared for more by other family members, such as siblings or grandparents. Nevertheless, the role of single mothers in providing positive reinforcement for children's behavior still seems important in the social learning process. Based on these findings, researchers suggest that single parents need social and economic support to help them shape their children's gender identity in the most effective way.